Editor's choice - VASCUNET rare vascular diseases: multicentre genetic investigation of patients with carotid paraganglioma - Erhart, Philipp; Cohnert, Tina; Siegl, Gregor K.; Anjum, Suzana; Matthys, Imke; Romagnoli, Silvia; Espada, Cristina López; Chiara, Maria-Dolores; Szatko, Alicja; Behrendt, Christian-Alexander; Ancetti, Stefano (European journal of vascular and endovascular surgery, 2025)
Objective - Carotid paragangliomas (CPGLs) are rare neuroendocrine tumours. Previous studies have emphasised the high prevalence of hereditary genetic variants. This study specifically examined the clinical course of CPGLs in patients with pathogenic disease causing genetic variants (PV) and non-specific non-pathogenic genetic findings (non-PV) currently not associated with CPGLs. - Methods - This was a multicentre, retrospective, exploratory study. Whole genome, exome, or gene panel sequencing was performed in participating centres in the clinical diagnostic setting. Genetic variants were described following appropriate reporting standards. Re-evaluation regarding their pathogenicity was performed according to the American College of Medical Genetics and Genomics guidelines. Individuals with benign, probably benign, or variants of unknown significance were assigned to the non-PV group, and individuals with probably pathogenic or pathogenic variants were assigned to the PV group. Relevant clinical variables and follow up data were collected to relate clinical outcomes to genetic findings. - Results - One hundred and seventy-three patients were analysed, of whom 45.1% had PVs in respective candidate genes for paraganglioma, including the succinate dehydrogenase (SDH) complex subunit D (n = 56), B (n = 17), C (n = 3), A (n = 1) and von Hippel-Lindau (n = 1) genes. Those with PVs were younger (median age 44 years vs. 60 years; p< .001), had a greater likelihood of multilocular paraganglioma manifestation (47 vs. 2; p< .001), and more frequently had local recurrences after surgical removal (20 vs. 1; p< .001). Tumour recurrence occurred a mean of 8.5 years following surgery. Bilateral CPGLs (39 vs. 2; p< .001) and a positive familial history of paraganglioma (28 vs. 4; p< .001) were associated with PVs. - Conclusion - Genetic variants, especially in the SDHD gene, were common and associated with worse CPGL outcomes, thus emphasising the benefit of genetic diagnostics and counselling.
Online verfügbar: 16. Juli 2025, Artikelversion: 11 December 2025
Gesehen am 19.02.2026